HERITABILITY OF THE NUMBER OF OVARIOLES IN HONEY-BEE WORKERS (APIS-MELLIFERA L) (HYM, APIDAE) - Diniz, JAF; Bueno, O. C.; Chaudnetto, J.; Malaspina, O. (Soc Brasil Genetica, 1993)
Narrow and broad sense heritabilities (h(2)) of the number of ovarioles in Apis mellifera L. workers were estimated using two distinct data sets, based on groups of half (queens inseminated by several drones) and super-sisters (single drone insemination). The values found are in the usual range for economically important characters (0.25-0.38).